Tardigrades from Nahuel Huapi National Park (Argentina, South America) with descriptions of two new Macrobiotidae species - Roszkowska, Milena; Stec, Daniel; Ciobanu, Daniel Adrian; Kaczmarek, Łukasz (Zootaxa, 2016)
In 31 samples of mosses and lichens collected in the Argentinean province of Río Negro, 657 tardigrades, 53 exuviae and 219 free-laid eggs were found. In total, 20 species were identified: Diphascon chilenense, Dip. mitrense, Echiniscus bigranulatus, Ech. corrugicaudatus, Ech. merokensis merokensis, Ech. testudo, Hebesuncus mollispinus, Hypsibius convergens, Macrobiotus cf. anderssoni, Mac. andinus, Mac. kazmierskii, Mac. patagonicus, Mesobiotus szeptyckii, Mes. pseudoblocki sp. nov., Milnesium argentinum, Mil. beatae, Mil. brachyungue, Mil. granulatum, Mopsechiniscus granulosus, Minibiotus pseudostellarus sp. nov. Of the two new species, Mesobiotus pseudoblocki sp. nov. is most similar to Mes. blocki, but it differs mainly by the lack of dentate lunules, smaller eggs and presence of reticular design on egg processes. Minibiotus pseudostellarus sp. nov. is most similar to Min. constellatus, Min. eichhorni, Min. sidereus or Min. vinciguerrae, but it differs from them by the presence of ‘pseudo-star’-shaped pores in the dorsal cuticle instead of fully developed ‘stars’ and by other morphometric characters.